Mechanical and biological behaviors of titania and tantala nanotubular arrays decorated with silver oxide on Ti-6Al-4V alloy / Masoud Sarraf - Masoud , Sarraf (2017)
Ti-6Al-4V alloy is among the most widely-used metallic materials for orthopedic and dental application due to its desirable features such as high strength and low density. However, Ti-6Al-4V cannot meet all of the clinical necessities owing to the lack of osseointegration required for implant longevity. The current research aimed to employ a novel surface modification for development of two different metallic oxides, including TiO2 and Ta2O5 nanotubes on biomedical-graded Ti-6Al-4V plates to improve the mechanical properties, tribological, corrosion behavior, osseointegration, and biocompatibility. The optimized self-organized TiO2 nanotubular arrays were fabricated by electrochemical anodization, followed by heat treatment at 500°C for 1.5 h to improve the adhesion strength of nanotubular arrays. On the other hand, for development of well-adherent Ta2O5 nanotubular coatings, an optimized PVD approach to deposit the thin films tantalum followed by a two-step anodization were performed. To improve the adhesion of nanotubular arrays, heat treatment was carried out at 450°C for 1 hour. Moreover, for improving the antibacterial properties of these two coatings, the Ag2O nanoparticles were decorated on the nanotube edges via PVD magnetron sputtering approach. The adhesion strengths between the coatings and substrates were evaluated using a microscratch tester under different conditions. The surface topography of the nanostructured coatings was examined by atomic force microscopy (AFM) and field emission scanning electron microscopy (FESEM). The X-ray diffractometry (XRD), energy dispersive X-ray spectroscopy (EDS) and X-ray electron spectroscopy (XPS) were also utilized to investigate the chemical composition of the developed thin films. The corrosion behavior, wear resistance, hardness, surface wettability, in-vitro bioactivity in simulated body fluids (SBF), antibacterial characteristics and biocompatibility of the products were also investigated in order to provide a better understanding of the specimen function in physiological conditions. The effective sputter yield of tantalum during the magnetron sputtering process was achieved with a DC power of 350W, temperature of 250°C and a deposition time of 6h. The anodization results showed that the time and electrolyte played a key role in the growth of TiO2 and Ta2O5 NTs as well as their microstructural evolution. The optimum pore sizes of TiO2 and Ta2O5 nanotubes were around 72nm and 40nm, while their lengths were identical (1μm). The scratch length, failure point, and adhesion strength of the annealed samples were 1000μm, 557.89μm, and 1814.28mN for TiO2 NTs as well as 1024μm, 863μm, and 2301mN for Ta2O5 NTs respectively. The annealed coating showed the highest wettability (lowest contact angle value), tribology (lowest coefficient of friction), corrosion resistance (highest percentage of protection efficiency) and highest hardness value among the specimens. In-vitro bioactivity tests before and after deposition of Ag2O NPs showed that the bone-like apatite layer was formed on nanotubular array coating as early as 1 day immersion in SBF, indicating the importance of nanotubular configuration of the in-vitro bioactivity. Finally, cell culture and antibacterial properties also showed promising results after decoration of Ag2O NPs. This multi-step approach could be considered for the design of various nanostructured titanium implant surfaces.